Forum speaker criticised for belittling student - Arukesamy, Karen (The Sun, 2013)
PETALING JAYA: Deputy Higher Education Minister Datuk Saifuddin Abdullah criticised a forum speaker for speaking in a "condescending" way and preventing a university student from expressing her views.